Trayectorias y ciclos de explotación sexual y trata para la explotación sexual de mujeres en la Amazonía peruana - Mujica, Jaris (2014)
The commercial sexual exploitation is a constant activity in the Peruvian Amazon. Around the river port of Pucallpa in ucayali region, the practice appears systematically: teenage attend taverns around the port, and those dedicated to the work of cooking camps logging, are victims of constant exploitation and many also of trafficking. this article aims to reconstruct the path of life and reproductive cycle of the forms of exploitation in a sample of 20 women, and focuses on: (i) evidence of seasonal forms of exploitation; (ii) the path of life of these women showing steps in a chain holding several stages and in different work areas; (iii) in this context, sexual exploitation and trafficking are not permanent phenomena, are concentrated in one point in the path and stopped to motherhood, between 19 and 25 years; (iv) with motherhood and matrilocal settlement, daughters and sons repeat the cycle and reproduce the chain.